The Effect of Anti-seizure Medications on the Propagation of Epileptic Activity: A Review - Khateb, Mohamed; Bosak, Noam; Herskovitz, Moshe (Frontiers in Neurology, 2021)
Propagation of epileptiform events is a highly interesting phenomenon from the pathophysiological point of view, as it involves several mechanisms of recruitment of neural networks. Extensive in vivo and in vitro research has been performed, suggesting multiple networks as well as cellular candidate mechanisms governing this process, including the co-existence of wave propagation, coupled-oscillator dynamics and more. The clinical importance of seizure propagation stems mainly from the fact that the epileptic manifestations cannot be attributed solely to the activity in the seizure focus itself, but rather to the propagation of epileptic activity to other brain structures. Propagation, especially when causing secondary generalizations, risks patients with recurrent falls, traumatic injuries and poor neurological outcome. Anti-seizure medications (ASMs) affect propagation in diverse ways and with different potencies. Importantly, in part of the drug-resistant patients, targeting seizure propagation may improve the quality of life even without major reduction in simple focal events. Motivated by the extensive impact of this phenomenon, we sought to review the literature regarding propagation of epileptic activity and specifically the effect of commonly used ASMs on it. Based on this body of knowledge, we propose a novel classification of ASMs into three main categories: major, minor, and intermediate efficacy in reducing the propagation of epileptiform activity.